Pareto-Optimal Resource Allocation in Wireless Powered Networks - Bouzinis, Pavlos S.; Vranas, Christos K.; Papanikolaou, Vasilis K.; Diamantoulakis, Panagiotis D.; Goudos, Sotirios K.; Karagiannidis, George K. (2020 9th International Conference on Modern Circuits and Systems Technologies, MOCAST 2020, 2020)
In this paper, the uplink of a wireless-powered network is investigated. More specifically, we focus on simultaneously maximizing the sum-throughput and minimum throughput of the network's users, for the case of non-orthogonal multiple access (NOMA) and time-division multiple access (TDMA), by optimizing the allocated time to energy harvesting and information transmission. Since this problem belongs to the category of multi-objective optimization, we transform it into a singleobjective problem, via the scalarization approach, aiming to obtain the Pareto Front. The proposed methodology facilitates the evaluation of the trade-off between the considered conflicted metrics. Finally, simulation results validate the effectiveness of the proposed methodology and provide useful insights for the network's performance.
Created from Fastlane, Scopus look-up
Keywords: Multi-objective optimization (MOO); Non-orthogonal multiple access (NOMA); Pareto front; Wireless powered networks (WPNs)